FAKTOR - FAKTOR YANG BERHUBUNGAN DENGAN PERILAKU SADARI PADA WANITA USIA SUBUR (WUS) DI WILAYAH KELURAHAN SEMPIDI MENGWI BADUNG - Pradnyandari, Ida Ayu Eni; Sanjiwani, Ida Arimurti; Astuti, Ika Widi (Coping: Community of Publishing in Nursing; Vol 10 No 1 (2022): Februari 2022DO - 10.24843/coping.2022.v10.i01.p11, 2022)
Self-Breast Examination (BSE) is the cheapest, easiest, and simplest way that every individual can do to detect signs and symptoms of breast cancer.  There are several factors that can affect the implementation of BSE examinations. This study aims to determine the factors associated with BSE behavior. This research is a descriptive correlation study with cross sectional design. The research sample was 30 woman of childbearing age in the Sempidi Village, Mengwi Badung, who were obtained through cluster sampling technique. Data analysis using Spearmen Rank with p value=0.05.  The results was no significant relationship between characteristic responden (age, marital status education level, and family history of breast cancer) (p=0.935, 0.782, 0.734, 0.702), knowledge (p= 0.121), attitude (p=0.822), information exposure (p=0.354), family support (0.368), peer support (p=0.618), health workers support (0.057) with BSE behavior. Hopefully based on the results of this study, nurses could provide education related to how to take proper BSE actions and could motivate women to do BSE on a monthly routine, atleast once a month.